Pengaruh Perilaku Organisasi Terhadap Produktivitas Kerja Ditinjau Dari Perspektif Psikologi Dan Ekonomi Islam - Dian Mayasari (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2026)
This study examines the relationship between organizational behavior and work productivity by integrating psychological and Islamic economic perspectives. To date, work productivity has largely been explained through conventional organizational psychology and economic efficiency approaches, while the dimensions of Islamic work values and ethics have not been explicitly integrated into organizational behavior frameworks. Using a literature review method and a conceptual analysis approach, this article examines how motivation, job satisfaction, organizational commitment, leadership, and organizational culture are associated with productivity, as well as how Islamic economic values, such as Islamic work ethic, the principle of itqan (performing work professionally), ihsan (striving for excellence), and justice (‘adl), strengthen these psychological mechanisms. The findings indicate that work productivity is a multidimensional phenomenon shaped by the interaction of employees’ psychological conditions, organizational behavior, and the spiritual and ethical values embraced by individuals. Integrating these three perspectives provides a more comprehensive conceptual framework for human resource management, particularly in organizations operating within an Islamic value-based context.